2015
DOI: 10.3390/ijms160715852
|View full text |Cite
|
Sign up to set email alerts
|

Chromium-Induced Ultrastructural Changes and Oxidative Stress in Roots of Arabidopsis thaliana

Abstract: Chromium (Cr) is an abundant heavy metal in nature, toxic to living organisms. As it is widely used in industry and leather tanning, it may accumulate locally at high concentrations, raising concerns for human health hazards. Though Cr effects have extensively been investigated in animals and mammals, in plants they are poorly understood. The present study was then undertaken to determine the ultrastructural malformations induced by hexavalent chromium [Cr(VI)], the most toxic form provided as 100 μM potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 51 publications
5
71
0
2
Order By: Relevance
“…Cr stress inhibits primary root elongation, in a dose‐dependent manner (Eleftheriou et al, ; Martinez‐Trujillo et al, ; Ortiz‐Castro et al, ). To investigate the effects of Cr(VI) on the inhibition of primary root elongation, 7 days old WT seedlings were exposed to 0, 50, 100, and 200 μM concentrations of Cr(VI) for 24 hr in ½ MS. All of the treated seedlings were transferred to fresh ½ MS for another 4 days, and the increase in the primary root length after treatment was measured and statistically analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cr stress inhibits primary root elongation, in a dose‐dependent manner (Eleftheriou et al, ; Martinez‐Trujillo et al, ; Ortiz‐Castro et al, ). To investigate the effects of Cr(VI) on the inhibition of primary root elongation, 7 days old WT seedlings were exposed to 0, 50, 100, and 200 μM concentrations of Cr(VI) for 24 hr in ½ MS. All of the treated seedlings were transferred to fresh ½ MS for another 4 days, and the increase in the primary root length after treatment was measured and statistically analysed.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, high Cr(VI) levels cause a decrease in seed germination, root elongation, leaf number, area and biomass, and greatly affect plant morphology as well as physiological, biochemical, and molecular processes (Huda et al, ; Kabir, ; Martinez‐Trujillo et al, ; Ortiz‐Castro, Martínez‐Trujillo, López‐Bucio, & Cervantes, ; Shanker, Cervantes, Loza‐Tavera, & Avudainayagam, ). Cr stress also exerts cytotoxic, genotoxic, and mutagenic effects in plant cells by causing cell cycle seizure, diminishing of cell division dynamics, derangement of the cytoskeleton, chromosomal aberrations, and stimulation of micronuclei formation (Eleftheriou et al, ; Patnaik, Achary, & Panda, ; Truta, Mihai, Gherghel, & Vochita, ). Root is the first plant organ that senses soil Cr(VI), typically responding to Cr‐exposure by inhibiting primary root elongation (Eleftheriou et al, ; Martinez‐Trujillo et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent changes induced by heavy metal are the generation of reactive oxygen species (ROS), that are involved in deterioration of plant physio-molecular attributes by the direct damages of nucleic acid, chloroplast structures and cell membranes [11, 12]. Enhanced level of ROS in different plant parts might be the imbalance between its production and inactivation by antioxidants that known as superoxide dismutase, peroxidase, catalase and ascorbate peroxidase, and also non enzymatic defense machinery called glutathione and carotenoids [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides the direct interaction of Cr with nucleic acids (e.g., promoting DNA-DNA cross-links), it has also been demonstrated that Cr(VI) may increase the generation of reactive oxygen species (ROS), leading to indirect cytotoxic effects [7][8][9][10]. The correlation of the antioxidant status with genotoxic damage remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%